AIMp1 Potentiates TH1 Polarization and Is Critical for Effective Antitumor and Antiviral Immunity - Liang, Dan; Tian, Lin; You, Ran; Halpert, Matthew M.; Konduri, Vanaja; Baig, Yunyu C.; Paust, Silke; Kim, Doyeun; Kim, Sunghoon; Jia, Fuli; Huang, Shixia; Zhang, Xiang; et al. (Frontiers in Immunology, 2018)
Dendritic cells (DC) must integrate a broad array of environmental cues to exact control over downstream immune responses including TH polarization. The multi-enzyme aminoacyl-tRNA synthetase complex component AIMp1/p43 responds to cellular stress and exerts pro-inflammatory functions; however, a role for DC-expressed AIMp1 in TH polarization has not previously been shown. Here we demonstrate that the absence of AIMp1 in bone marrow-derived DC (BMDC) significantly impairs cytokine and costimulatory molecule expression, p38MAPK signaling, and TH1 polarization of co-cultured T-cells while significantly dysregulating immune-related gene expression. These deficits resulted in significantly compromised BMDC vaccine-mediated protection against melanoma. AIMp1 within the host was also critical for innate and adaptive antiviral immunity against influenza virus infection in vivo. Cancer patients with AIMp1 expression levels in the highest tertiles exhibited a 70% survival advantage at 15-years post-diagnosis as determined by bioinformatics analysis of nearly 9,000 primary human tumor samples in the TCGA database. These data establish the importance of AIMp1 for the effective governance of antitumor and antiviral immune responses.